2021
DOI: 10.4014/jmb.2103.03041
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluation of Bifidobacterium breve IDCC4401 Isolated from Infant Feces for Use as a Commercial Probiotic

Abstract: Previously, our research group isolated Bifidobacterium breve IDCC4401 from infant feces as a potential probiotic. For this study, we evaluated the safety of B. breve IDCC4401 using genomic and phenotypic analyses. Whole genome sequencing was performed to identify genomic characteristics and investigate the potential presence of genes encoding virulence, antibiotic resistance, and mobile genetic elements. Phenotypic analyses including antibiotic susceptibility, enzyme activity, production of biogenic amines (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Lactate exists in two stereoisomeric forms, namely the L-form and D-form. Some strains of LAB, including Lactobacillus and Bifidobacterium genera, produce both D(−)-lactate and L(+)-lactate [10,49]. Since D(−)-lactate cannot be metabolized in the human gut, the excessive production and accumulation by gut bacteria could potentially lead to D-lactate acidosis and short bowel syndrome [50].…”
Section: Lactate Production Of the Probiotic Strainsmentioning
confidence: 99%
“…Lactate exists in two stereoisomeric forms, namely the L-form and D-form. Some strains of LAB, including Lactobacillus and Bifidobacterium genera, produce both D(−)-lactate and L(+)-lactate [10,49]. Since D(−)-lactate cannot be metabolized in the human gut, the excessive production and accumulation by gut bacteria could potentially lead to D-lactate acidosis and short bowel syndrome [50].…”
Section: Lactate Production Of the Probiotic Strainsmentioning
confidence: 99%
“…In recent years, studies have found that breast milk is an important source of oral (Ruiz et al, 2019) and gastrointestinal bacteria in breastfed infants and this has an important impact on the early intestinal flora and the health of infants (McGuire and McGuire, 2015). With the maturity of strain isolation technology and culture conditions, a large number of probiotics, such as Lactobacillus rhamnosus (Li et al, 2020), L. plantarum, Bifidobacterium breve (Choi et al, 2021), and Bifidobacterium longum (Hikaru et al, 2020) have been isolated from breast milk and infant feces.…”
Section: Optimization Of the Test Conditions For Bile Salt Tolerancementioning
confidence: 99%
“…Bifidobacterium breve is notable for its antimicrobial properties against human pathogens, non-cytotoxic nature, and immunostimulatory abilities. This probiotic strain is commonly used in children as studies have demonstrated that B. breve in the GIT of infants could help reduce diarrhea occurrence, prevent allergic diseases, and protect infants from developing necrotising enterocolitis [ 6 - 10 ]. Building on its success in pediatric applications, there is a growing interest in exploring the potential use of B. breve for a wider population [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%